1971
DOI: 10.1136/jcp.24.3.263
|View full text |Cite
|
Sign up to set email alerts
|

Endocardial fibroelastosis in children with special reference to the lesions of cardiac ganglia

Abstract: SYNOPSIS In all cases of primary endocardial fibroelastosis investigated diffuse degenerative changes in the ganglion cells were detected. Thickened endocardium was formed by the proliferation of mesenchymal cells located under the endothelial endocardium and of the mesenchyme surrounding the necrobiotic muscle cells. In some cases 'axial' vacuolar degeneration, necrobiosis, and necrosis of muscle cells, interstitial oedema, and dilatation of capillaries and lymphatic spaces were found in the whole myocardium.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1972
1972
1994
1994

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Black-Schaffer (1957) suggested that the myocardial changes resulted from mechanical factors in association with a dilated ventricle. Zoltowska (1971) studied cardiomyopathy in infants who also had endocardial fibroelastosis. She showed degenerative changes in the nerve ganglia of the heart and considered these changes of aetiological significance.…”
mentioning
confidence: 99%
“…Black-Schaffer (1957) suggested that the myocardial changes resulted from mechanical factors in association with a dilated ventricle. Zoltowska (1971) studied cardiomyopathy in infants who also had endocardial fibroelastosis. She showed degenerative changes in the nerve ganglia of the heart and considered these changes of aetiological significance.…”
mentioning
confidence: 99%